Rhythmic Auditory Stimulation as an Adjuvant Therapy Improved Post-stroke Motor Functions of the Upper Extremity: A Randomized Controlled Pilot Study - Tian, Rujin; Zhang, Bei; Zhu, Yulian (Frontiers in Neuroscience, 2020)
Objectives: To explore whether rhythmic auditory stimulation (RAS) could improve motor functions of post-stroke hemiparetic upper extremity. Design: A prospective, randomized controlled, assessor-blinded pilot study. Methods: Thirty stroke patients were randomly distributed into the RAS group (N=15) and the control group (N=15). Both groups received regular therapies. The RAS group received additional 30 minutes’ RAS training, while the control group received additional 30 minutes’ regular therapies for 5 days per week for 4 weeks. The Fugl-Meyer Assessment - Upper Extremity (FMA-UE), Wolf Motor Functional Test (WMFT), Barthel Index (BI) were used. The co-activation interval and co-contraction index were calculated from surface electromyography (sEMG) recordings on the affected biceps and triceps during elbow flexion and extension. Assessments were performed before and after the treatments. Results: Significant improvements in motor functions were observed within both groups (p < 0.05 in the FMA-UE, WMFT, BI, respectively), also between groups after the treatments (higher scores in the RAS group, all p < 0.05 except for p = 0.052 in the FMA-UE; group x time interaction, all p < 0.05). Statistical significance was found in the co-activation interval between groups after the treatments (lower in the RAS group; p = 0.022 during elbow extension; p = 0.001 during elbow flexion; group x time interaction, p < 0.05 only during elbow extension). No statistical significance was found in the co-contraction index between groups; an inversed pattern of changes was observed between groups supported by relatively higher increments in the triceps recruitments to the biceps. Conclusion: Using RAS in task-oriented exercises was effective in moderating co-contraction, facilitating task-oriented movements of the hemiparetic upper extremity, and improving ADLs among those who had emerging isolated joint movements. The effects were evident on sEMG possibly by adjusting the balance of recruitments between the agonist and the antagonist.